2016
DOI: 10.1093/jxb/erw069
|View full text |Cite
|
Sign up to set email alerts
|

Pepper CabZIP63 acts as a positive regulator duringRalstonia solanacearumor high temperature–high humidity challenge in a positive feedback loop with CaWRKY40

Abstract: HighlightCabZIP63, indirectly activated by CaWRKY40, positively modulates transcription of CabZIP63 and CaWRKY40, enhances the binding of CaWRKY40 to its target promoters, and, therefore, increases resistance to Ralstonia solanacearum and thermotolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 89 publications
8
62
0
Order By: Relevance
“…This indicated that CaBPM4 silencing aggravated P. capsici infection in pepper by diminishing the defense system of pepper plants. A similar result was also observed in CabZIP63-silenced plants, where the transcript levels of the defense-related genes CaPR1 and CaDEF1 were significantly lower than those in the control pepper plants under R. solanacearum infection [54]. Similarly, CaPTI1 and CanTF silencing also altered the expression levels of CaPR1 [55], CaDEF1 [56], and CaSAR82 [57] as well as the root activity of silenced plants relative to those in control plants [38,45].…”
Section: Discussionsupporting
confidence: 68%
“…This indicated that CaBPM4 silencing aggravated P. capsici infection in pepper by diminishing the defense system of pepper plants. A similar result was also observed in CabZIP63-silenced plants, where the transcript levels of the defense-related genes CaPR1 and CaDEF1 were significantly lower than those in the control pepper plants under R. solanacearum infection [54]. Similarly, CaPTI1 and CanTF silencing also altered the expression levels of CaPR1 [55], CaDEF1 [56], and CaSAR82 [57] as well as the root activity of silenced plants relative to those in control plants [38,45].…”
Section: Discussionsupporting
confidence: 68%
“…Apart from the TGAs, several bZIPs from other subfamilies were also involved in disease resistance. For example, CabZIP2 and CabZIP63 were found to enhance the resistance to P. syringae and R. solanacearum in pepper (Lim et al, 2015;Shen et al, 2016), LrbZIP1 was involved in defense responses against Fusarium oxysporum in Lilium (Zhang et al, 2014), and bZIP10 modulates basal defense and cell death following infection in Arabidopsis (Kaminaka et al, 2006). In this study, we found that StbZIP61 functioned in defense against P. infestans.…”
Section: Discussionmentioning
confidence: 55%
“…syringae and R . solanacearum in pepper (Lim et al ., ; Shen et al ., ), LrbZIP1 was involved in defense responses against Fusarium oxysporum in Lilium (Zhang et al ., ), and bZIP10 modulates basal defense and cell death following infection in Arabidopsis (Kaminaka et al ., ). In this study, we found that StbZIP61 functioned in defense against P .…”
Section: Discussionmentioning
confidence: 99%
“…Pepper bZIP TF, CaAIBZ1, interacting with and degraded by CaASRF1 (C. annuum ABA-Sensitive RING Finger E3 ligase 1), positively modulated ABA signaling and the drought stress (Joo et al, 2018). Additionally, CabZIP63 was up-regulated by Ralstonia solanacearum inoculation at high temperature-high humidity and acted as a positive regulator in this process by regulating the expression of CaWRKY40 (Shen et al, 2016). Collectively, the bZIP TFs family in pepper is an important gene family involved in stress response along with a crucial role in growth and development.…”
Section: Introductionmentioning
confidence: 99%